Dual-Band Frequency Selective Surface-Backed Reflectarray for High-Speed Ka-Band Satellites - Gulseren, Ahmet Hulusi; Alparslan, Aytac; Tokan, Nurhan Turker (MDPI, 2024)
A dual-band, dual-polarized frequency selective surface (FSS)-backed multilayer reflectarray antenna is designed for 5G high-speed satellites operating at Ka-band uplink and downlink frequencies (20/30 GHz). A reflectarray antenna system consists of two reflectarrays that are separated from each other by an FSS layer that behaves as a planar bandpass filter at Ka-band satellite uplink frequencies. Each reflectarray antenna is designed with dual-polarized unit cells. In order to achieve a uniform phase distribution across the reflectarray surface, physical dimensions and positions of the unit cells with a fixed periodicity are carefully chosen. The FSS conductor is etched to the bottom layer of the 30 GHz reflectarray substrate to save cost and weight. The reflectarray performance is analyzed by using CST Microwave Studio and array theory. A prototype is fabricated, and the results are experimentally verified. The gain of the reflectarray is measured as 21.13 dBi and 26.94 dBi at 20 and 30 GHz, respectively. A crosspol level of more than 35 dB is observed at both frequencies. The simulated and measured results show that the proposed reflectarray is suitable for high-speed Ka-band satellites.
Keywords: 5G high speed satellite; dual band; FSS; Ka-band; multilayer; reflectarray antenna; CIRCULARLY-POLARIZED REFLECTARRAY; BROAD-BAND; ANTENNA; DESIGN; ARRAY; Chemistry; Engineering; Materials Science; Physics